Silbury Hill
Excavation of the mound was carried out in 1777 and again in 1849, but nothing of importance was discovered. It is hoped that excavations will reveal its origins, but at present, the only certain facts are that it served as the alignment of the nearby Roman Road, and that until overtaken by mechanically placed spoil heaps, it was the largest man-made mound in Europe.